Application of the Game Scrabble to Improve English Vocabulary in Early Children - Nopriansyah, Untung; Permata Hati, Intan; Rafitasari, Hesti (JOYCED: Journal of Early Childhood Education, 2024)
The Kindergarten Assalam 1 Sukarame Bandar Lampung faces the issue of low English vocabulary skills. To address this, Scrabble was introduced as a game-based learning tool to enhance their English language skills. The research employed Classroom Action Research (CAR) using the Kemmis and McTaggart model, which includes planning, implementation, observation, and reflection stages. The study was conducted in two cycles, each consisting of four meetings. Data collection methods included observation, interviews, and documentation. The findings showed that Scrabble effectively facilitated English learning in early childhood, creating a lively and engaging learning environment while stimulating various learning opportunities. Initial observations indicated that the children's vocabulary skills were below the expected standards. However, after the first cycle, their skills improved to the "Starting to Develop" category. By the end of the second cycle, their vocabulary skills had further increased to the "Developing According to Expectations" (BSH) category. In conclusion, the use of Scrabble significantly improves English vocabulary skills in early childhood at Kindergarten Assalam 1 Sukarame Bandar Lampung. Keywords: Early childhood; English; vocabulary; game; Scrabble.